2023
DOI: 10.3390/ijms24098433
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plant Transcription Factors in the Fight against Plant Viruses

Abstract: Plants are vulnerable to the challenges of unstable environments and pathogen infections due to their immobility. Among various stress conditions, viral infection is a major threat that causes significant crop loss. In response to viral infection, plants undergo complex molecular and physiological changes, which trigger defense and morphogenic pathways. Transcription factors (TFs), and their interactions with cofactors and cis-regulatory genomic elements, are essential for plant defense mechanisms. The transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 181 publications
0
12
0
Order By: Relevance
“…For instance, we identified the functional known gene CUC2 ( AT5G53950 ) which is an elite polyphenotype gene ( Figure 4A ). In A. thaliana , AT5G39610 is associated with salt resistance ( Zhao et al., 2022 ), AT3G49530 is associated with drought resistance ( Kim et al., 2012 ), and AT5G08790 is associated with disease resistance ( Viswanath et al., 2023 ). In rice, LOC_OS04G38720 influences plant height and grain weight ( Chen et al., 2015 ; Jiang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we identified the functional known gene CUC2 ( AT5G53950 ) which is an elite polyphenotype gene ( Figure 4A ). In A. thaliana , AT5G39610 is associated with salt resistance ( Zhao et al., 2022 ), AT3G49530 is associated with drought resistance ( Kim et al., 2012 ), and AT5G08790 is associated with disease resistance ( Viswanath et al., 2023 ). In rice, LOC_OS04G38720 influences plant height and grain weight ( Chen et al., 2015 ; Jiang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported that plant TFs participate in viral infection by interacting with viral proteins (Viswanath et al., 2023 ). The changes in transcription levels of these TFs during RSV infection have been validated, but it is still unknown whether these TFs can directly interact with RSV proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors (TFs) play crucial roles in plant defense mechanisms and innate immunity through interactions with cofactors and cisacting elements. The transcriptional regulation of certain TFs can enhance plant defenses against viral infections ( Viswanath et al, 2023 ). Therefore, it is plausible that miRNAs may regulate the viral infection process by targeting TFs.…”
Section: Resultsmentioning
confidence: 99%